He`s ours, not yours! Reinterpreting national identity in a post-socialist context - Bartoluci, S.; Doupona, M. (International Review for the Sociology of Sport, 2020)
This paper focuses on the relationship between sport, national identity and the media in the post-socialist nation-states of Croatia and Slovenia. It describes what has changed during the eight years since Jakov Fak, a Croatian-born Slovenian biathlete, changed his citizenship and began competing for the Slovenian national team. It also examines how the perception of Jakov Fak as an athlete and of his success has changed through time in different socio-political circumstances - in 2009 and 2010 when he competed for Croatia, and after 2010 when he began competing for Slovenia. To analyse this case we have used different media interpretations of Jakov Fak case, analysing four sports events: the Biathlon World Championships in South Korea (13-22 Feb 2009) and Germany (1-11 Mar 2012), and the Olympic Games in Canada (11-18 Feb 2010) and South Korea (9-25 Feb 2018). The results of discourse analysis show that in the case of Jakov Fak in the years 2009 and 2010, the public was provoked by and exposed to national symbolism, especially in political discourse. The media discourse did change between 2012 and 2018, and discourse typical of civic nationalism began to dominate. Two types of nationalism are mixed in a post-socialist context.